Dementia, Care and Elder Abuse in Late Twentieth-Century Detective Fiction: Reginald Hill's Exit Lines and Michael Dibdin's The Dying of the Light. (September 2021) - Orr, David M. R.
Abstract : Dementia-themed detective fiction has become something of a trend. This article extends the critical history of this development to a period often ignored by scholars, considering two noteworthy examples from the late twentieth century: Reginald Hill's (1984) Exit Lines and Michael Dibdin's (1993) The Dying of the Light . Through textual analysis and historical contextualisation, the article shows how these novels raise disturbing questions about dementia care, older people's rights and therefore their citizenship. Both texts make sophisticated use of the distinctive affordances of the detective fiction genre to comment on failings of care in their time, belying common assumptions that the productive engagement of detective fiction with dementia is a recent innovation.